2017
DOI: 10.1007/s40368-017-0277-9
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of a RPE activation key: Why do these accidents still happen?

Abstract: Ingestion of foreign bodies is a potential complication during orthodontic treatment. These types of accidents may cause serious consequences to the patient, especially if there is a pre-existing systemic condition, such as heart disease or respiratory problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
2
0
6
Order By: Relevance
“…[ 23 ] According to Pantuzo et al . [ 24 ] (2017), the key slipped from the parent's fingers and the patient swallowed it during the activation of the appliance at home. Parents admitted that they felt overconfident and as a result they neglected to use dental floss to tie the rapid palatal expansion (RPE) key, as it was advised.Finally, Mahto et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 ] According to Pantuzo et al . [ 24 ] (2017), the key slipped from the parent's fingers and the patient swallowed it during the activation of the appliance at home. Parents admitted that they felt overconfident and as a result they neglected to use dental floss to tie the rapid palatal expansion (RPE) key, as it was advised.Finally, Mahto et al .…”
Section: Resultsmentioning
confidence: 99%
“…Actually, both retrospective and longitudinal studies of ingestion and aspiration have shown that its frequency is around 0.004% and that aspiration is rarer than ingestion. [ 24 ] In most of the cases, natural excretion of the foreign object is observed. In only 1% of the cases complicated problems occur, which may result in death.…”
Section: Discussionmentioning
confidence: 99%
“…Dentro de los efectos adversos reportados en la literatura encontramos efectos inherentes a la técnica, y otros prevenibles, tales como la bacteremia transitoria y la deglución accidental del dispositivo de activación del expansor. (6,7,9) El profesional debe ser capaz de realizar una completa anamnesis para tener identificados a los pacientes de alto riesgo de desarrollar endocarditis bacteriana al utilizar la aparatología de ERM y de poder actuar preventivamente, utilizando profilaxis antibiótica. (8,9) La escasa bibliografía encontrada no permite realizar un buen análisis estadístico, debido a la heterogeneidad de los estudios, se hace más complejo la tarea de comparar las diferentes investigaciones.…”
Section: Discussionunclassified
“…Cuando esto ocurre, el instrumento puede transitar por el tracto intestinal sin incidentes hasta ser eliminado en el excremento; o también ser causante de serias complicaciones, (6) tales como: obstrucción de la vía aérea o gastrointestinal, perforación de órganos, hemorragia interna, sepsis o incluso la muerte. (7) La situación siempre debe ser motorizada cercanamente. Si el paciente no reporta sintomatología o padece algún tipo de enfermedad intestinal, se recomienda seguimiento y la eliminación del objeto ocurrirá sin dificultades.…”
Section: De Activación Del Expansor Maxilarunclassified
See 1 more Smart Citation